Large Spectral Shift of Reflected Radiation From Laser Plasmas Generated by High Contrast KrF Laser Pulses - Kovács, Zsolt; Gilicze, Barnabás; Szatmári, Sándor; Földes, István B. (Frontiers in Physics, 2020)
Increasing absorption up to more than 90% with increasing intensity was observed in boron and gold laser plasmas heated by KrF laser pulses of high, but still non-relativistic, intensity. The pulses of 700 fs duration had a temporal contrast of 12 orders of magnitude; thus, the laser pulse of more than 1018 Wcm−2 intensity hit the steep surface of the boron and gold targets. Blue shift of the reflected radiation refers to extreme high acceleration resulting in velocities above 5 × 105 ms−1. Brunel absorption and ponderomotive effects are shown to play an important role in the observed phenomena.